Effects of environmental strategy, environmental uncertainty and top management's commitment on corporate environmental performance: The role of environmental management accounting. (10th April 2018) - Latan, Hengky; Chiappetta Jabbour, Charbel Jose; Lopes de Sousa Jabbour, Ana Beatriz; Wamba, Samuel Fosso; Shahbaz, Muhammad
Abstract: This study aims to examine the effect of the combination of corporate environmental strategy, top management commitment, and environmental uncertainty, with a focus on the role of environmental management accounting (EMA), on corporate environmental performance. Using an online survey, we collect the sample data of 107 responses in ISO 14001 certified companies listed on the Indonesia Stock Exchange. The empirical evidence shows that there is a positive and significant influence between those organizational resources (corporate environmental strategy, top management commitment, and environmental uncertainty) on the use of EMA, which in turn can improve the environmental performance of companies. These findings indicate that EMA is a useful and important tool for providing information to achieve superior corporate environmental performance in Indonesian firms and the findings also suit for companies operating in other countries in terms of developing capabilities with regards to perceived environmental uncertainty to be able to manage EMA tools and, as a consequence, to improve organizational environmental performance.